2016
DOI: 10.1080/19443994.2015.1043496
|View full text |Cite
|
Sign up to set email alerts
|

LCA application in the assessment of new technologies of industrial effluents treatment

Abstract: A B S T R A C TLife cycle assessment (LCA) is a technique often used to assess the impact of technological processes on the environment and on human health. It can be also used as a tool to assess environmental micropollutants. The possibility to conduct full LCA of particular stages of technology by means of appropriate LCA software can allow for reliable identification of the sources of chemical hazards in the environment, with particular focus on the source and the amount of macro and micropollutants. Full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Environmental life cycle assessment (LCA) in the evaluation of the impact of potential products on the environment is a technique that primarily allows the possibility of conducting a full life-cycle analysis, and thus the production processes, as well as credible and reliable identification of the environmental risks and environmental impact of new products. The new generation of waste-based polymers are water-soluble and have the properties of flocculants reducing the pollution parameters in mine waters (Bajdur et al 2016(Bajdur et al , p. 1058. The results of the analysis of research carried out using the LCA technique to assess the impact of modified polymeric waste (polystyren and novolaks) on the environment confirmed that LCA is an appropriate method to assess the environmental impact of new products (flocculants) used in the process of industrial wastewater treatment.…”
Section: Analysis Of Research Resultsmentioning
confidence: 99%
“…Environmental life cycle assessment (LCA) in the evaluation of the impact of potential products on the environment is a technique that primarily allows the possibility of conducting a full life-cycle analysis, and thus the production processes, as well as credible and reliable identification of the environmental risks and environmental impact of new products. The new generation of waste-based polymers are water-soluble and have the properties of flocculants reducing the pollution parameters in mine waters (Bajdur et al 2016(Bajdur et al , p. 1058. The results of the analysis of research carried out using the LCA technique to assess the impact of modified polymeric waste (polystyren and novolaks) on the environment confirmed that LCA is an appropriate method to assess the environmental impact of new products (flocculants) used in the process of industrial wastewater treatment.…”
Section: Analysis Of Research Resultsmentioning
confidence: 99%
“…The analysis was performed in the SimaPro version 8.2 computer program, which enables the analysis using 68 evaluation methods. Many authors, including the authors of this publication, used the Ecoindicator 99 method to assess environmental impact [23][24][25][26]. However, due to the fact that it has been replaced by the ReCiPe method, the use of this method is proposed.…”
Section: Methodology Of Lca Analysismentioning
confidence: 99%
“…In Poland, the LCA technique is used to assess the production of alternative flocculants and the treatment of industrial wastewater with their use. The paper [89] describes the use of the LCA technique to identify the sources and assess the impact on the environment of the stage of the potential production of new-generation flocculants synthesized from post-production polystyrene waste and the stage of wastewater treatment with the use of synthesized products. In turn, in [90], the LCA technique was used to evaluate the impact of a new flocculant used in the treatment of wastewater from the metallurgical industry, taking into account the impact of the flocculant production process on the environment.…”
Section: Review Of Environmental Impact Analyses Of Wastewater Treatment Plants Conducted In Various Parts Of the World With Particular Ementioning
confidence: 99%